2012
DOI: 10.1097/mpg.0b013e31824ac64c
|View full text |Cite
|
Sign up to set email alerts
|

Can Colonic Manometry Studies Be Done on the Day of Colonic Motility Catheter Placement?

Abstract: Colonic manometry studies can be conducted as early as 4 hours following catheter placement with either propofol or sevoflurane used for anesthesia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 23 publications
1
18
0
Order By: Relevance
“…Patients, research staff and hospital administrators alike do not appreciate prolonged, overnight studies. While the data utilized in this study were from recordings commencing the day after colonoscopic placement of the catheter, we have since shown that colonic motility is detectable within hours of catheter placement, a fact also confirmed by others 30 …”
Section: Discussionsupporting
confidence: 81%
“…Patients, research staff and hospital administrators alike do not appreciate prolonged, overnight studies. While the data utilized in this study were from recordings commencing the day after colonoscopic placement of the catheter, we have since shown that colonic motility is detectable within hours of catheter placement, a fact also confirmed by others 30 …”
Section: Discussionsupporting
confidence: 81%
“…24 We used sevoflurane anesthesia protocol as we have shown previously that anesthesia protocol does not alter colonic motility study findings. 25 In our study octreotide was overall well tolerated. Six patients had mild discomfort with administration of subcutaneous octreotide.…”
Section: Discussionmentioning
confidence: 79%
“…On the other hand, Ammoury et al. found no difference in the MI or study interpretation when comparing results after catheter placement or the next day . However, their study population does not seem to represent patients with significant defecation disorders as the majority of the subjects (17/20) had a normal CM already on day 1 that remained normal on day 2.…”
Section: Discussionmentioning
confidence: 91%
“…Some centers perform the study on the same day right after catheter placement under anesthesia and others perform it the following day. A previous study showed that there is no difference . Another study suggested that there may be more colonic motor events recorded the day after anesthesia .…”
Section: Introductionmentioning
confidence: 92%